Challenges and Experiences of Online Evaluation in Courses of Civil Engineering during the Lockdown Learning Due to the COVID-19 Pandemic - Marcos García-Alberti; Fernando Suárez; Isabel Chiyón; Juan Carlos Mosquera Feijoo (MDPI AG, 2021)
As a consequence of the global health emergency in early 2020, universities had to tackle a sudden shift in their teaching-learning strategies so that the preset competences could be fulfilled. This study presents the learning outcomes of the implemented tasks, student experiences, and feedback, as well as some reflections from the instructors with a holistic perspective of the courses due to the adopted measures and adaptations. Six courses taught at civil engineering degrees of three universities, two from Spain and one from Peru, were analyzed. The teaching and evaluation strategies are described, and some reflections are made by comparing the student's performance with the previous course. Though the shift to online learning had to be made from day to day, with no time for preparation, the experience has proved that online learning can be beneficial in some aspects and has probably come to stay, although some other aspects are difficult to replace with respect to face-to-face learning, especially students' engagement and motivation. The significance of this study relies on a description of the challenges that arose due to the global public health and an assessment of the results of the implemented strategies to account for both teaching and evaluation in modules of civil engineering. After the acquired experience, new questions have arisen, e.g., what type of content is (and what is not) adequate or suitable for online exams? What features have come to stay? Has higher education taken a step forward to tomorrow's education?